Sociolingvistická situace psaných slovanských jazyků v 1. polovině 18. století - Knoll, Vladislav (Slavia Occidentalis, 2017)
The main aim of the article is to present a complex image of the diversity, use and functions of written Slavonic idioms in the first half of the 18th century, which is the period that shortly precedes the creation of the modern national languages. This detailed view shows that the number of the written varieties was much larger, and the function structure of the single languages and varieties in each speech community was more complex than now. The article also discusses the methodological issues linked to the studies on the pre-national languages and tries to find the common patterns of variety hierarchy in each of the main cultural areas of the Slavonic world.